Social media interactions, purchase intention, and behavioural engagement: The mediating role of source and content factors - Onofrei, George; Filieri, Raffaele; Kennedy, Lorraine (Journal of business research, 2022)
Consumers increasingly interact with multimedia posts shared by peers on social media (SM) platforms. Drawing upon service-dominant logic (SDL) and the information adoption model (IAM), we examine the relationship between Consumer-to-Consumer’s (C2C) social media interactions (SMIs, Facebook and Instagram) and consumers’ intention (i.e., purchase intention) and behaviour (i.e., behavioural engagement (BE), liking, sharing, commenting), considering the mediating role of source (i.e., source homophily, credibility) and content factors (i.e., content quality). The results indicate that SMIs influence perceived source credibility, source homophily, content quality, and consumers’ purchase intention. Furthermore, source credibility and homophily predict BE and partially mediate the relationship between SMI and BE, whereas both homophily and post quality partially mediate the relationship between SMI and purchase intention. This study integrates SDL, the IAM, and source homophily, showing their application to C2C social media conversations, contributing to both theory and practice.